AquaNet - Chemical parameters from Stortjärn AquaNet platform - Svartberget Research Station (Swedish University of Agricultural Sciences, 2020)
Data contains chemical parameters from grab samples taken from the AquaNet mesocosms.
Svartberget Research Station (2020). AquaNet - Chemical parameters from Stortjärn AquaNet platform, 2017-06-05–2017-09-25 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/3xqimOeSKoO9m0D5GVvXkgUx
Keywords: SITES; Chlorophyll; Fish; Nitrogen Compounds; Phosphorous Compounds; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap